The effect of exercises using a factory device to develop the speed of the visual and auditory motor response of youth volleyball players - Subhan Sakhi, Ali; Haydar Dawood, Hassan; Akram Sabaa, Qais (International Journal of Psychosocial Rehabilitation, 2020)
The first chapter included the introduction to the research and its importance, and the researchers dealt with the advantages of the volleyball game, which has specific features that distinguish it from other group games, and the importance of the sense of sight and hearing. To get them to the best possible level. As for the research problem, it is through the researchers’ experience and their observation that the kinetic response is being trained in traditional ways and means, so they decided to prepare exercises with a device manufactured with visual and auditory stimuli to develop the speed of the kinematic response of young volleyball players. As for the objectives of the research, they were: 1- The manufacture of an electronic device with visual and audio stimuli to develop the speed of the kinematic response of youth volleyball players. 2- Preparing exercises using a factory device to develop the speed of the visual and auditory movement response of youth volleyball players As for imposing research, it was: 1- There are statistically significant differences between the results of the pre and posttests and in favor of the post tests. As for the second chapter, the researchers used the experimental method using the method of one experimental group with two pre and posttests. The research sample was chosen by the deliberate method. They are the young players of the Police Sports Club, whose number is (14) players aged (16-18) years.